2015
DOI: 10.1097/qad.0000000000000720
|View full text |Cite
|
Sign up to set email alerts
|

A standards-based approach to quality improvement for HIV services at Zambia Defence Force facilities

Abstract: A standards-based approach to quality improvement proved effective in supporting healthcare managers and providers to deliver ART and PMTCT services in accordance with evidence-based standards in a health system suffering from staff shortages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…In this study, significant and consistent increases in compliance with SBM-R standards were observed over time. Comparable results have been recorded in other studies [20]. …”
Section: Discussionsupporting
confidence: 90%
“…In this study, significant and consistent increases in compliance with SBM-R standards were observed over time. Comparable results have been recorded in other studies [20]. …”
Section: Discussionsupporting
confidence: 90%
“…We grouped approaches into 4 main categories with support from experts in the Quality of HIV Care Technical Working Group (Fig. 1): health systems approaches using QI methods (n = 20), 21,22,2426,29–43 standard-based methods that use QI tools to improve performance gaps (n = 2), 17,23 campaigns that use QI methods (n = 1), 28 and QI learning networks including collaboratives (n = 6). 15,16,1820,27 Initiatives were performed in 13 LMICs, including South Africa, 15,19,20,28 Vietnam, 16,35 Zambia, 17,23 Nigeria, 18,27 Uganda, 21,22,31,36,40 Mozambique, 21,22 Namibia, 21,22,29,34,42,43 Haiti, 21,22,24,32,36,41 Thailand, 25,26 Nicaragua, 33 Kenya, 38 Tanzania, 37 and Guyana, 34,39 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The 2 citations that used standard-based methods only reported on acceptability of the intervention (2 published and 0 gray literature). 17,23 The studies initially sought to define performance criteria relevant to the context, before using outside support to measure pre-existing performance gaps (in relation to the new standards), which are subsequently addressed and reassessed. In both studies, the authors indicated that health care worker perceptions of their work environment were positively impacted by the intervention, whereas they declined in comparison sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing performance monitoring team at health facilities were instrumental in using the health facility data for weekly review and performance improvement. A similar intervention in Zambia helped staff identify weaknesses, develop interventions for improvement, mobilize resources, and strengthen support systems to improve ART and prevention of mother-to-child HIV transmission services [ 13 ]. In our intervention, major issues identified at the health facility and sub-city level were escalated to AACAHB for further attention.…”
Section: Discussionmentioning
confidence: 99%